369Womeńs empowerment benefits early childhood numeracy-literacy in 26 African countries. (2nd September 2021) - Coll, Carolina; Ewerling, Fernanda; Lynch, John; Raj, Anita; Victora, Cesar; Barros, Aluisio
Abstract: Background: Every year more than 200 million children under-five years fail to achieve their full developmental potential in low- and middle-income countries. We explored whether mothers' empowerment is associated with early childhood development in 26 African countries. Methods: We used data from Demographic and Health Surveys and Multiple Indicator Cluster Surveys ranging from 2010 to 2018. Four developmental domains were assessed among children aged 36-59 months using the Early Childhood Development Index: literacy-numeracy, physical, learning and socioemotional. Women's empowerment in attitude to violence, social independence and decision-making was evaluated using the SWPER Global, a validated survey-based index. We used logistic regression to estimate the associations between mother's empowerment level in each domain and the development of their children controlled by wealth. Results: Across all countries, 15·1% of the children were on track in the literacy-numeracy domain, 92·3% in physical, 81·3% in learning and 67·8% in socio-emotional. The odds of a child being on track in literacy-numeracy increased by 11%, 34% and 18%, with a one standard deviation increase in the scores of attitudes to violence, social independence and decision-making domains of empowerment, respectively. No effect of empowerment was observed for the other domains of child development in most countries. Conclusions: We found a consistent and positive effect of mothers' empowerment on the literacy-numeracy domain of child development. The null effects in other developmental domains may be related to lower variability in these outcomes, or to specific effects on literacy-numeracy. Key messages: Womeńs empowerment has a potential to improve child development and their future human capital